Effects of Typhoon Mangkhut on a Monsoon Evergreen Broad-Leaved Forest Community in Dinghushan Nature Reserve, Lower Subtropical China - Li, Yuelin; Mwangi, Brian; Zhou, Shun; Liu, Shizhong; Zhang, Qianmei; Liu, Juxiu; Chu, Guowei; Tang, Xuli; Zhang, Deqiang; Wei, Shimin; Lie, Zhiyang; Wu, Ting; et al. (Frontiers in Ecology and Evolution, 2021)
Sensitivity to climate change is one of the key features of the Dinghushan National Nature Reserve that is located in the lower subtropical China. Having faced typhoon Mangkhut in 2018, there emerged a need to study the effects that the typhoon had on the evergreen broad-leaved forest community in Dinghushan. The forest composition data for 2015, 2018, and 2020 was used in this study. The aim was to establish a scientific basis for the restoration of natural forests that have the ability to withstand strong weather phenomena such as typhoons and the hypothesis stated that typhoon Mangkhut had a long-term detrimental effect on the forest community in Dinghushan forest. The results showed that trees that have a DBH of less than 5 cm and a height of less than 2 m were more prone to damage during a severe weather events. In 2015, there was a total of 5,682 trees per hectare while in 2018 there was a total of 5,022 trees per hectare showing a decline in the number of trees per hectare of 660 due to the typhoon. Number of trees in each DBH class, height class, total above ground dry weight and average tree height was also lower in 2018 as compared to 2015 and 2020. The species abundance was also adversely affected with a loss of 672 species per hectare in 2018 compared to 2015. In 2020, about 83% of all trees had a DBH of less than 5 cm and an average height of 3.8 m making up a large proportion of trees that could be damaged if another storm occurred of similar or greater magnitude as the one that hit the region in 2018. Of interest was the forests remarkable ability to bounce back as there is an increase in biomass when 2018 is compared to 2020. The results support the hypothesis of the study. It is therefore of utmost importance that strategies be put in place to protect this ecosystem and others of a similar nature, by employing the use of natural forests that have great resilience against typhoons.